Estrutura da demanda de arroz, ao nível de atacado, no município de Santarém, Pará, em 1969 - Brandt, Sérgio Alberto; Fagundes de Sousa, Antônio; Martins Rezende, Alberto; da Paz Puga Rebello, Armando (Revista Ceres, 2025)
This study is concerned with the several variables influencing the demand for rice at the wholesale level in the Município of Santarém, state of Pará, Brazil. Santarém is the principal producing center of the state and also a terminal for the production of the other regions in the Amazonas Valley. The study was conducted in order to determine the demand elasticity of rice in the long and short run. A census was conducted among the wholesalers that operate in the rice market in the above mentioned município, including the Rice Producers Cooperative of Santarém.